2011
DOI: 10.30935/cedtech/6055
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Information and Communication Technology Based Approach and Laboratory Training Model of Teaching on Achievement and Retention in Chemistry

Abstract: The purpose of the present study was to investigate the effectiveness of the Information and Communication Technology (ICT) based approach and the Laboratory Training Model of Teaching (LTM) chemistry. It strived to determine whether the ICT or the LTM would be more effective with respect to the male and female students' overall as well as component-based achievement in chemistry and their retention of learning. The sample of the study consisted of 120 seventh standard students from two English-medium elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Carrillo, Onofa and Ponce (2010) carried out an experimental study on information technology and students' achievement and they found that ICT has a positive effect on the achievement scores in mathematics test, but failed to increase achievement scores in language test. Badeleh and Sheela (2011) inferred that generally to study chemistry, component based achievement, retention of learning and comprehension, ICT was more successful than the laboratory training model of teaching.…”
Section: Teaching Through Ictmentioning
confidence: 99%
“…Carrillo, Onofa and Ponce (2010) carried out an experimental study on information technology and students' achievement and they found that ICT has a positive effect on the achievement scores in mathematics test, but failed to increase achievement scores in language test. Badeleh and Sheela (2011) inferred that generally to study chemistry, component based achievement, retention of learning and comprehension, ICT was more successful than the laboratory training model of teaching.…”
Section: Teaching Through Ictmentioning
confidence: 99%
“…Research suggests that use of ICT as an instructional strategy increases academic achievement of learners (Badeleh & Sheela, 2011;Coates, Humphrey, Kane & Vachris, 2004;Ziden, Ismail, Spian, & Kumutha, 2011). Thus, the 21st century teaching and learning demands new strategies that could enhance three domains; cognitive, effective and psychomotor in the learners.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the differences in proficiency development that arise between SIM and CON group is that the 3D-computer simulation training can be regarded as an activity that enables the students to, not practically hands-on but virtually, experience a specific concept (cf. the laboratory training model described by Badeleh & Sheela, 2011). The aim for the SIM group to position an object requires manipulation and observation that captures students' attention and guides them toward relevant areas.…”
Section: Discussionmentioning
confidence: 99%